Impact of textual enhancement on EFL grammar learning in Bangladesh - Jahan, Akhter (Department of Literature and Linguistics, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Textual Enhancement (TE) can be distinguished as the focus on form procedure that intends to increase the input saliency in any kind of texts (written or oral) so that learners can notice targeted forms in a meaning oriented context and thereby acquire those items' form-function mappings (Schmidt, 1995, 2001; Sharwood Smith, 1991, 1993). It has been suggested by Lee (2007) and White (1998) that this implicit procedure would be able to facilitate language acquisition process of those learners who have pre-knowledge regarding targeted forms. In spite of having long term pre-exposure to English, most of the tertiary learners of Bangladesh encounter problems in using the target language accurately. Therefore, this fourteen-week long experimental study aims to investigate whether or not TE can facilitate those learners' noticing, intake and acquisition of form to function mappings of the target forms related to certain uses of articles, tense, subject verb agreement, modal auxiliaries and voice in the noun and the verb phrase constructions. Six pre-tests, immediate post-tests and delayed post-tests were conducted in this study. One hundred undergraduate level learners from Bangladesh were involved and were divided into enhanced, non-enhanced and control groups. Data were elicited through the following tasks: a note taking, a reading comprehension, two grammar-based activity, a certainty judgement test and a meta-linguistic awareness battery; besides the tasks, the researcher included four noticing questions. The TE procedure ensured that all six pairs of forms were emboldened in twelve corresponding texts. The results of the study revealed that multiple exposure to TE over a period of time would be effective in increasing the noticing of the targeted forms. A salient point worthy of emphasis is that such exposure would facilitate the acquisition of only those forms which are salient in terms of meaning and frequency, and simple in respect of structure. In this study, one form that fulfilled the criteria was the targeted modal auxiliaries; performance related to this form showing significant improvements and sustainability.